Synthesis of biofilm from Polylactic Acid (PLA) and Green Algae [MORPHOLOGIGAL ANALYSIS OF CHLORELLA] / Nur Zaitiey Shazreen Mohd Zainudin - Mohd Zainudin, Nur Zaitiey Shazreen (2023)
In this era, the usage of plastic packaging is on the high demand as many people are using it. Along with the consequences, the usage of plastic packaging raises environmental concern as it put our Earth on danger. Hence, we have come for an alternative to make a biodegradable biofilm by using solution casting method. In this research, Polylactic Acid (PLA) was used because it melts more easily because it has a lower melting point. Not only that, polylactic acid also is used because it comes from a renewable source. The spirulina-algae was used because it is biodegradable and costeffective. For the casting method, the PLA and spirulina-algae are dissolved in dichloromethane (DCM) and being casted for the analysis. Fourier Transform Infrared Spectroscopy test (FTIR) was used to indicate the presence of organic and inorganic compounds in the biofilm produced. Thermal Gravimetric Analysis (TGA) shows that the mass of spirulina decreases as temperature increases. The last analysis is morphological analysis which has been done that shows the surface of the spirulina.